2006
DOI: 10.1103/physreva.73.013823
|View full text |Cite
|
Sign up to set email alerts
|

Level crossings in a cavity QED model

Abstract: In this paper I study the dynamics of a two-level atom interacting with a standing wave field. When the atom is subjected to a weak linear force, the problem can be turned into a time dependent one, and the evolution is understood from the band structure of the spectrum. The presence of level crossings in the spectrum gives rise to Bloch oscillations of the atomic motion. Here I investigate the effects of the atom-field detuning parameter. A variety of different level crossings are obtained by changing the mag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In the effective mass approach, this means that the atom is considered to move freely with the effective mass. Larson et al [5] showed that the effective mass is independent of time t and the time evolution of the atom-field system is governed by a time-independent Hamiltonian, when the influence of the gravitational field is not taken into account. The effective mass in the presence of the gravitational field defined as in [5], is in the form of the equation:…”
Section: The Effective Mass For the Jcm In The Presence Of The Gravit...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the effective mass approach, this means that the atom is considered to move freely with the effective mass. Larson et al [5] showed that the effective mass is independent of time t and the time evolution of the atom-field system is governed by a time-independent Hamiltonian, when the influence of the gravitational field is not taken into account. The effective mass in the presence of the gravitational field defined as in [5], is in the form of the equation:…”
Section: The Effective Mass For the Jcm In The Presence Of The Gravit...mentioning
confidence: 99%
“…The effective mass approach is one of these theoretical schemes. Larson et al investigated the effect of the cavity on the atomic motion [5]. They introduced the effective mass parameter based on the Floquet theory [6][7][8].…”
Section: Introductionmentioning
confidence: 99%